Electric Coolant Pump for Automobile - Design and Performance Optimization - K. Balasubramanian, J. Sureshkumar, R. Vishvak, K. Vaidheeswaran, M. Risheek Shankar (International Journal of Advanced Science and Technology, 2020)
Most of the cars driven on the road today are cooled by employing a mechanically driven coolant pump, which is considered as the conventional method, where the engine drives the pump. If the pump is driven electrically, instead of being driven mechanically, specific parameters like engine performance, fuel economy (which also when improved reduces CO2 emissions), engine shut-down cooling, and cabin cooling, can be improved. And also, in the future when cars become electrically driven, a mechanical coolant pump cannot be used. Hence the development of an electric coolant pump is highly essential for the drastically changing auto industry. Moreover, automotive electronics have become an appealing area of study for engineers today. The present study primarily focuses on the design and performance optimization of an electrically driven automobile coolant pump, by comparing the motor performance both in simulation and in experimentation in a test rig. For performing the simulation to test motor performance theoretically, commercially available software was used. And for practical experimentation, a test rig designed specifically to test electric coolant pumps and vacuum pumps was used to test the practical performance. Then the results obtained from both simulation and experimentation is compared.